Distribution of indium, germanium, gallium and other minor and trace elements in polymetallic ores from a porphyry system: The Morococha district, Peru - Benites, D. (2021)
This study was economically supported by the Peruvian CONCYTEC-FONDECYT-World Bank project 107-2018-FONDECYT-BM-IADT-AV, the FONCAI-0023-2019 project granted by the Pontificia Universidad Católica del Perú (PUCP) and a Huiracocha Ph. D grant to D.B. granted by the PUCP. Pan American Silver Corp. provided field and logistical support and access to the mine area. Pan American Silver Corp. Morococha staff is most gratefully acknowledged, particularly Julio Zárate and Rubén Diaz. We appreciate the technical support by Xavier Llovet (CCiT-UB) during the acquisition of EPMA data, and by Peter Tollan (ETHZ) during the acquisition of LA-ICP-MS data. We are grateful to Fredrik Sahlström, Max Frenzel, and Editor-in-Chief Franco Pirajno for their constructive comments which significantly improved the manuscript.